Coping with Permanent Liminality: Social Understanding and Action through Theatre in Late Communist Hungary - Arpad Szakolczai (Social Sciences, 2023)
Theatre is the modern liminoid equivalent of ritual liminality, according to Victor Turner. It is also, like most arts, a Janus-faced phenomenon: on one hand, it is a way to systematically infect the public with mimetic desire and rivalry (this is the aspect emphasised, quite rightly, by Plato and René Girard); on the other, it also enables the public expression of views about the contemporary state of social and political life that otherwise would be difficult to speak about, or even censored. As an example, this article will turn to the 1970s in Hungary, when the communist regime had become much softened, though at the same time generated the impression, in everyone, that it would last forever. More concretely, it will first shortly present and analyse the quite unique story of the Kaposvár theatre, which during the decade changed, through a peculiar combination of ‘liminal’ factors, from a boring provincial spectacle to the number one theatrical event of the country, avidly followed by students and intellectuals, especially from the capital. An epilogue is devoted to the masterly article by Elemér Hankiss, the most important and influential intellectual living then in Hungary who became, for a time, the consensus president of the Hungarian Television after the collapse of communism. It exposes the infantilising character of communist power by analysing a series of theatrical performances staged in a leading Budapest theatre in the late 1970s. Infantile adults are evidently caught in a permanent liminality, so Hankiss shows how theatre indeed was a main instrument in diagnosing the worst aspect of life under communist rule, its permanent liminality, reinforcing uncertainty and hopelessness.